Adenosquamous Carcinoma of the Pancreas: a Rare Entity - Kharel, Ashish; Shrestha, Shashank; Shrestha, Rashes; Bhattarai, Niraj; Acharya, Bigyan; Thakur, Binay (Nepalese Journal of Cancer, 2022)
Pancreatic Adenosquamous Carcinoma is a rare subtype of pancreatic cancer. Here we present a 51 year old man who presented with features of obstructive jaundice. Radiological imaging studies revealed the presence of solid pancreatic mass. He underwent pancreaticoduodenectomy – superior mesenteric artery (SMA) first approach. Postoperative period was complicated with prolonged ascitic drainage. Histological analysis suggested adenosquamous carcinoma with 30% squamous components, pT2N0M0. Patient is being planned for adjuvant chemotherapy.